Smart Finance: Leveraging Artificial Intelligence for Sustainable and Equitable Budget Management in Schools - Phumphuang, Prakapat; Panyarat, Tatchtacha (วารสารนวัตกรรมการบริหารและการจัดการศึกษา, 2025)
This conceptual article examines the integration of artificial intelligence (AI) in school budget management and introduces the AI-Enhanced Budget Cycle Framework (AIBCF) - a six-phase model designed to support financial sustainability, operational efficiency, and equitable resource allocation in educational settings. Drawing on current literature and real-world applications, the paper identifies key AI tools such as machine learning, predictive analytics, and fuzzy logic that enhance each stage of the budgeting process. Key findings include the development of the AIBCF framework, which systematically applies AI technologies to needs assessment, planning, allocation, execution, monitoring, and feedback. Conceptual contributions highlight how AI transforms traditional budgeting from reactive to proactive systems, promoting transparency and data-driven decision-making. This study offers a novel integrative model to guide future research and implementation in educational financial management.